Методы и механизмы геттерирования кремниевых структур в производстве интегральных микросхем - Pilipenko, V. A.; Gorushko, V. A.; Petlitskiy, A. N.; Ponaryadov, V. V.; Turtsevich, A. S.; Shvedov, S. V. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
Increasing the degree of integration of hardware components imposes more stringent requirements for the reduction of the concentration of contaminants and oxidation stacking faults in the original silicon wafers with its preservation in the IC manufacturing process cycle. This causes high relevance of the application of gettering in modern microelectronic technology. The existing methods of silicon wafers gettering and the mechanisms of their occurrence are considered.